Controls on and impacts of the diurnal cycle of deep convective precipitation. (22nd November 2013) - Hohenegger, C.; Stevens, B.
<x xml:space="preserve">Abstract</x> [1] Cumulus parameterizations have well‐known difficulties in capturing the diurnal cycle of tropical precipitation. This study explores the degree to which prescribed variations in cumulus mixing (entrainment/detrainment) can affect the precipitation diurnal cycle over a certain region and contribute to major climatic biases. This is achieved by artificially adjusting cumulus mixing rates as a function of time and location. It is found that variations in cumulus mixing can easily control the phase and amplitude of the oceanic precipitation diurnal cycle but not the total amount. The situation is different over land: the precipitation timing cannot be controlled by the mixing rates alone. Moreover, shifting the precipitation peak from noon to later times reduces the precipitation amplitude due to the strong diurnal cycle in convective triggering. This shift is accompanied by a reduction in net shortwave radiation and in latent heat flux (transpiration), which acts to reduce the total precipitation amount. The use of fixed SST and the absence of vegetation prevent a similar behavior over ocean. Climatic biases, as e.g., expressed by the location and structure of precipitation objects, seem not to be sensitive to the precipitation timing as long as the daily averaged precipitation remains similar. The differences are also smaller than differences induced by more structural changes performed to the convection scheme. Systematic but weak dependencies can mainly be isolated over the maritime continent, in the land‐to‐ocean precipitation ratio, in the location of the Atlantic ITCZ, in the surface fluxes over land, and in the net shortwave radiation.